ANALISIS PEMANFAATAN MEDIA CANVA DALAM MENINGKATKAN MINAT BELAJAR MATA PELAJARAN BAHASA INGGRIS PADA SISWA KELAS 3 DI SD NEGERI KETILENG 2 KOTA CILEGON - Hairul Umam; Desty Endrawati Subroto; Kurniati Rahmadani (STKIP Subang, 2026)
This study analyzes the utilization of Canva media in increasing students' interest in learning English for 3rd-grade students at SD Negeri Ketileng 2 Cilegon. Using a qualitative descriptive approach with observation, interviews, and documentation, the results show a significant increase in student engagement after implementing Canva. Students became more active, creative, and motivated in creating posters and visual materials for the